Measuring and Meeting Service Quality in Professional Accounting Services - Sulaiman, Noor Adwa; Zakaria, Zarina (Asian Journal of Accounting Perspectives, 2009)
The objective of this paper is to assess the service quality of management advisory services offered by accounting firms in Malaysia. The SERVQUAL technique is used to identify the gap between the expectations and perceptions of customers on the actual service received. The quality function deployment technique is then used to identify elements that can be improved to meet customer expectations and address the quality gap in MAS. The results of this study show that there is an overall service quality gap perceived by the customers. Thus, improvements are required across all four service quality dimensions (credibility, competence, responsiveness and reliability). The results also identify several key elements of improvement that should be focused on by the accounting firms to meet customer expectations and narrow the service quality gap.